Reassessing the Role of the Communist Party in a Socialist Society: The Case of 1960s Czechoslovakia - Šíma, Jan; Broučková, Kristina (Dějiny – teorie – kritika, 2025)
This article examines the efforts of the Communist Party of Czechoslovakia (CPCz) to discursively anchor its leading role amid the shifting socio-political terrain of the 1960s. While the party’s position was clearly defined during the revolutionary stage, the guidelines for exercising its leadership in the socialist society officially declared in 1960 were far less clear. This article focuses on how, over the following years, political discourse increasingly incorporated sociological findings about the structure of socialist society, influencing conceptions of the party’s leading role. Yet, once 1968 hit, as the people’s demands grew in response to the often-unsatisfactory lived experience in socialist society, the CPCz faced not only the challenge of defining its role but also the necessity of defending it to counteract public discontent. This article thus examines the rhetorical strategies employed by the political elite in the early months of 1968 to navigate this challenge. It argues that two rhetorical figures dominated the discourse: the recurrent term “unity” and the emerging term “trust.” These terms allowed the political elite to strike a precarious balance between maintaining continuity and striving for a radical departure from the status quo through hegemonic strategy.